Enhancement of Antarctic stratospheric aerosol layer in winter: Possible contribution of Aitken particle growth - Iwasaka, Yasunobu (1986)
P(論文) The lidar measurements at Syowa Station (69°00′S, 39°35′E), Antarctica revealed that the content of stratospheric particles increased noticeably and that particle shape possibly was of ice crystal in winter. The increase in number of particles with large size, in addition to the deposition growth of ice particles, possibly contributes to the stratospheric particulate matter increase during winter. departmental bulletin paper